Language Contact: The Emergence of Pidgins and Creole Englishes - Efendi, Arapa (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2017)
Pidgins and creoles (P/Cs) languages are generally emerged from the practical situation of interlinguistic communication. Thus, for the sake of communication some people may unconsciously create a new language which has simpler structure than the normal language. Concerning that issue, this paper focuses to describe pidgins and creoles (P/Cs) languages including its characteristics. Further, this paper tries to explore the developmental stages of pidgin and creoles languages, and to find out some factors which might cause them to emerge. However, the scope of this paper is limited under the discussion of pidgin and creoles based English or known as pidgin and creoles Englishes.